Functional segregation of rostral and caudal hippocampus in associative memory - Vorobiova, Alicia Nunez; Feurra, Matteo; Pavone, Enea Francesco; Stieglitz, Lennart; Imbach, Lukas; Moiseeva, Victoria; Sarnthein, Johannes; Fedele, Tommaso (Frontiers in Human Neuroscience, 2025)
IntroductionThe hippocampus plays a crucial role in episodic memory. Given its complexity, the hippocampus participates in multiple aspects of higher cognitive functions, among which are semantics-based encoding and retrieval. However, the “where,” “when” and “how” of distinct aspects of memory processing in the hippocampus are still under debate.MethodsHere, we employed a visual associative memory task that involved encoding three levels of subjective congruence to delineate the differential involvement of the rostral and caudal portions (also referred as anterior/posterior portions) of the human hippocampus during memory encoding, recognition and associative recall.ResultsThrough stereo-EEG recordings in epilepsy patients we show that associative memory is reflected by rostral hippocampal activity during encoding, and caudal hippocampal activity during retrieval. In contrast, recognition memory encoding selectively activates the rostral hippocampus. The temporal dynamics of memory processing are manifested by gamma power increase, which partially overlaps with low-frequency power decrease during encoding and retrieval. Congruence levels modulate low-frequency activity prominently in the caudal hippocampus.DiscussionThese findings highlight an anatomical segregation in the hippocampus in accordance with the contributions of its partitions to associative and recognition memory.